(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study investigated the determinants of poor academic performance in Mathematics at the West Africa Senior School Certificate Examination (WASSCE) in Kenema City, Sierra Leone. A sequential explanatory mixed-methods design was employed. The quantitative phase analyzed WASSCE results (2018-2022) from a stratified random sample of eight secondary schools (N=6,132 pupils). We employed multilevel logistic regression to model the odds of achieving a credit pass, controlling for pupil, teacher, and school-level factors. The qualitative phase involved validated surveys with 1,489 SSS3 pupils and 70 teachers, alongside interviews and observations. Quantitative results confirmed a systemic performance crisis, with significant yearly and between-school variance. Key predictors of failure included teacher qualification level (Odds Ratio [OR] for unqualified teachers = 0.38, p<.01), pupil attitude score (OR=1.24 per unit increase, p<.001), and socioeconomic status (OR for low-income=0.45, p<.01). A notable performance spike in 2021-2022 was partially explained by pandemic-related exam adjustments. Qualitatively, a high proportion (82.86%) of teachers were "trained but unqualified," fostering over-reliance on passive pedagogy, which exacerbated pupil disengagement. The study concludes that performance is shaped by a complex interaction of factors best understood through a Socio-Ecological lens. We propose a phased, three-year implementation plan for stakeholder-specific interventions targeting teacher upskilling, resource provision, and mindset change.